2003
DOI: 10.1093/oxfordjournals.rpd.a006265
|View full text |Cite
|
Sign up to set email alerts
|

Target cells in internal dosimetry

Abstract: Data related to radium induced bone sarcomas in humans are used as a method of defining target cells on bone surfaces and in the bone marrow. The differential distribution of radiation induced bone sarcoma types, with a high ratio of non-bone producing, mainly fibroblastic tumours, challenges the ICRP concept that the bone lining cells are target cells. Multipotential mesenchymal stem cells are located within the range of alpha particles and are the most likely target cells for the fibroblastic type of bone sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 0 publications
1
24
0
1
Order By: Relevance
“…Recent studies have indicated that the osteoprogenitor cells are localized near the bone surfaces, perhaps out to 50 mm from the trabecular surfaces (20,21). The findings of the present study are thus congruent with the growing recognition of the functional and spatial interaction of hematopoiesis and osteoprogenitors.…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies have indicated that the osteoprogenitor cells are localized near the bone surfaces, perhaps out to 50 mm from the trabecular surfaces (20,21). The findings of the present study are thus congruent with the growing recognition of the functional and spatial interaction of hematopoiesis and osteoprogenitors.…”
Section: Discussionsupporting
confidence: 90%
“…It is planned to revisit the validation task during the third phase of Project 1.1 (2010)(2011)(2012). Nevertheless, because the difference in external doses between TRDS-2000 and TRDS-2009D is basically small, it is reasonable to remind now of the results of our validation study for the Metlino residents performed as a part of Project 1.1 in 2003, 2006a.…”
Section: Validation Of External Dosesmentioning
confidence: 91%
“…It is possible that gross tissue damage is a necessary precursor to the initiation of rectal cancer, as appears to be the case for bone tumors (Gössner 2003). On the other hand, verification of target-cell location in the large intestine performed in a new ICRP human alimentary tract model (HATM) results in one order of magnitude decrease of dose coefficients for strontium radionuclides (ICRP 2006).…”
Section: Analysis Of Changes In Individual-dose Estimatesmentioning
confidence: 99%
“…In der Kontrollgruppe fanden sich allerdings ebenfalls mehr beobachtete CLL (sechs Fälle) als erwartet (2,8 Fälle; p = 0,07). Zwar gibt es mittlerweile Hinweise, dass auch dieser Typ der Leukämie strahleninduziert sein kann [26], die erhöhten Raten in Expositions-und auch Kontrollgruppe sprechen allerdings für die bereits bekannte generelle Assoziation von CLL mit dem Morbus Bechterew [6,34].…”
Section: Diskussionunclassified